The Effect of Mindfulness on Aggressive Behavior: A Meta-Analysis - Utami, Yasmin Adlina Heraputri; Yudiarso, Ananta (Universitas Islam Indonesia, 2023)
Aggressive behavior is a concerning issue that requires attention because of its negative effects on victims. It can manifest in various forms and can be carried out by anyone, at any time. The reasons and conditions that contribute to this behavior are closely linked to an individual’s level of mindfulness. Previous studies have shown that mindfulness can minimize this aggressive behavior. Therefore, this meta-analysis study aims to examine the effect of mindfulness on aggressive behavior. It involves 17 scientific studies with 6,722 respondents. The entire results showed a negative relationship between mindfulness and aggressive behavior. The study obtained an effect-sized result of -.270 with 95% Cl [-.336, -.205] and I2 of 83.89%. This implies that mindfulness and aggression behavior have a small effect size due to other variables, factors, and mediators. These other variables and moderators need to be included in future studies to describe other factors more related to this behavior. Furthermore, similar studies need to be added to confirm the correlation between mindfulness and aggression behavior.